2008
DOI: 10.4049/jimmunol.180.10.6663
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Gene Expression Profile of Marginal Zone versus Follicular B Cells and Idiotype Positive Marginal Zone B Cells before and after Immunization with Streptococcus pneumoniae

Abstract: Marginal Zone (MZ) B cells play an important role in the clearance of blood borne bacterial infections via rapid T‐independent IgM responses. We have previously demonstrated that MZ B cells respond rapidly and robustly to bacterial particulates. To determine the MZ‐specific genes that are regulated to allow for this rapid response, resting MZ and Follicular (FO) B cells were sort‐purified and analyzed via DNA microarray. We identified 181 genes that were significantly different between the two cell populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
7
42
0
Order By: Relevance
“…We observed a progressive increase in expression as B cells mature in the bone marrow. In the spleen, we found Klf3 levels to be lowest in MZ cells, in agreement with previous data comparing gene expression in purified FO and MZ B cell populations (56). This might imply that low levels of Klf3 promote MZ cell development.…”
Section: Klf3 Is Differentially Expressed During B Cell Development Asupporting
confidence: 80%
“…We observed a progressive increase in expression as B cells mature in the bone marrow. In the spleen, we found Klf3 levels to be lowest in MZ cells, in agreement with previous data comparing gene expression in purified FO and MZ B cell populations (56). This might imply that low levels of Klf3 promote MZ cell development.…”
Section: Klf3 Is Differentially Expressed During B Cell Development Asupporting
confidence: 80%
“…The resulting set of 2737 genes associated with MZ B cells versus follicular B cells included most of those previously identified in a similar comparison. 33 As shown in supplemental Figure 2B, using these 2737 genes to determine the relatedness of follicular and MZ B-cell subsets from normal and transgenic mice, we found that transgenic MZ B cells, and, surprisingly, transgenic follicular B cells, clustered together with normal MZ B cells. This was unlike in a purely computed (unsupervised) clustering where follicular and MZ B cells were grouped together irrespective of being transgenic or not (supplemental Figure 2A).…”
Section: Klf3 Induces a Mz B-cell Signature Within Follicular B Cellsmentioning
confidence: 99%
“…In addition, haemopoietic stem and progenitor cells, megakaryocytes and mast cells display medium levels of expression. Additional recent micro-array-based studies have also indicated that, within the population of splenic B cells, there is preferential expression of D6 in marginal zone B cells compared with follicular B cells [77]. It is not easy to implicate these cells, especially B cells and HSC in chemokine scavenging at inflamed sites and so we are currently attempting to define alternative roles for D6 on these cell types.…”
Section: D6 Expression By Leukocytesmentioning
confidence: 99%